Assessment of the monitoring and evaluation team of oyo state agency for the control of adds (2016)
This study analysed the monitoring and evaluation officers of Oyo State Agency for the Control of Aids (QYSACA) to enable improvements in HIV programming in Oyo State and other parts of Nigeria. It was a correlation research which treated three research questions. Simple random sampling and purposive sampling techniques were used for selecting 33 persons and managers of the local action committees on AIDS used for the study. The Assessment of State Monitoring and Evaluation team’s Knowledge - ASOMEK (KR(20)= 0.73) was the instrument used for data collection, which were-then analysed using descriptive statistics t-test and ANOVA at 0.05 level of significance. The study found no significant difference between the performance, of male and female members of the monitoring and evaluation team in the capacity building workshop. But there was significant difference in, the performance of M&E team based on- their educational qualifications f(6.26) - 3.425; p<0.05. Holders of BSc : (Nursing) performed, better (x=13.18) than both ordinary and higher diploma holders in public health (x=13.00). It was recommended that, an M&E work plan .be developed and that it should articulate the roles and responsibilities of ail in a participatory-manner.